From Text to Texture: Elevating English Teaching Through Visual Literacy Skills - Irasuti, Irasuti; Ruminda, Ruminda; Bachtiar, Bachtiar (Universitas Cokroaminoto Palopo, 2024)
In an era dominated by visual media, this study examines the effects of visual literacy training on the ability of English teachers at Kalam Kudus Elementary School in Bali to create effective teaching materials. Utilizing a one-group pretest-posttest design, 21 teachers underwent training in the CRAP (Contrast, Repetition, Alignment, Proximity) principles. Data collected from pre-and post-tests, alongside a supplementary questionnaire, indicated a notable enhancement in teachers' visual literacy, with an average Gain score of 74.15%. Although the training was deemed moderately effective, educators experienced a significant boost in their understanding and application of visual design principles, contributing to the creation of more engaging educational content. The study highlights the need for continued professional development in visual literacy to address ongoing challenges, emphasizing its importance in improving educational practices.